Assessment of two-phase dissolution system as a guide in drug formulation: The furosemide case: Furosemide biphasic dissolution test - Hussein, Mohammed Abdulzahra; Sahib, Mohanad Naji (Iraqi Journal of Pharmaceutical Sciences, 2024)
The performance and the quality control of a drug may be evaluated using different approaches. Dissolution test is a corner stone in these processes. However, many issues appeared when using monophasic dissolution system like keeping the sink condition and/or described the in-vivo performance for Class II and IV drugs. Therefore, this study was to evaluate the biphasic dissolution system as discriminatory tool to differentiate between manufacture process and different excipient use for Class IV drug. Furosemide was prepared by two different methods: direct compression and wet granulation. Different excipients (acid and base) were used for each method. Furthermore, two commercially available products (Lasix® and generic product FA) were used for comparison with the prepared formulation. All formulations were evaluated for physical properties like hardness, friability and disintegration. Monophasic and biphasic dissolution tests were carried out for all formulas. All physical properties of the prepared tablets were within acceptable values. The dissolution rates of all three types of formulas (brand, generic, and prepared formulation) were identical under monophasic conditions. The similarity factor was more than 50 and difference factor less than 15. On the other hand, the biphasic dissolution profiles (aqueous phase, organic phase and overall dissolution media) showed significant differences between all prepared formulations and the brand product. Moreover, the two phase system still had the ability to show the similarity between brand and generic product. Furthermore, the direct compression method showed lower release than wet granulation method. Similarly, the acid excipients showed higher release than the basic one. As a conclusion, the biphasic dissolution system showed an excellent discriminatory power. Moreover, this approach was superior over conventional dissolution system regarding identifying variations in production processes and excipients content.